2003
DOI: 10.1046/j.0004-8666.2003.00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of umbilical artery Doppler velocimetry in the monitoring of pregnancy in women with pre‐existing diabetes

Abstract: Umbilical artery Doppler velocimetry is not a good predictor of adverse perinatal outcomes in diabetic pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…As such there is currently no consensus over the definition of IUGR; however, commonly used definitions include estimated fetal weight below the 10th, 5th, or 3rd percentile for gestational age, consistent with our methods (17). The utility of umbilical artery Doppler has been demonstrated in pregnancy complicated by IUGR and preeclampsia; however, it has not been validated in a diabetic population (34)(35)(36)(37). This may explain why we found no difference in the S/D ratio in our study, whereas Giles et al (20) have previously shown that a high S/D ratio correlates with significant reduction in small artery vessel count on placental histopathology.…”
Section: Discussionmentioning
confidence: 99%
“…As such there is currently no consensus over the definition of IUGR; however, commonly used definitions include estimated fetal weight below the 10th, 5th, or 3rd percentile for gestational age, consistent with our methods (17). The utility of umbilical artery Doppler has been demonstrated in pregnancy complicated by IUGR and preeclampsia; however, it has not been validated in a diabetic population (34)(35)(36)(37). This may explain why we found no difference in the S/D ratio in our study, whereas Giles et al (20) have previously shown that a high S/D ratio correlates with significant reduction in small artery vessel count on placental histopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting reports on the value of PI in diabetic pregnancy may well stem from the fact that high and low risk populations are studied combined including gestational diabetes [2,5]. Wong et al concluded that type 1 diabetes is the only group with sufficient risk to warrant repeat investigation [6]. Mean glycemic values are significantly higher in diabetic women with pathologic PIs suggesting that hyperglycemia causes increase in placental resistance [4].…”
Section: Discussionmentioning
confidence: 99%
“…Wong et al find that if the umbilical measurements are carried out within 2 weeks of delivery, they are significantly associated with adverse perinatal outcome. In their study 80% of pregnancies with elevated umbilical PI have adverse outcome if the PI is measured within one week before delivery [6]. We had an even narrower interval between measurements and delivery (≤ 3 days) because of the timed delivery in most cases; 50% were induced and 50% delivered by cesarean.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 30% of women with adverse perinatal outcome had abnormal umbilical artery Doppler measurements. The authors thus concluded that the performance of umbilical artery Doppler was not satisfactory even in this group of high risk women with pre-existing diabetes, and that it was not a good predictor of adverse perinatal outcome (Wong et al, 2003). To investigate whether complications were higher in diabetic pregnancies with cardiac maladaptation, fetal, uteroplacental and echocardiographic examinations were compared in the second and third trimester between diabetic and healthy pregnant women.…”
Section: Fetal Umbilical Artery Dopplermentioning
confidence: 99%